The Role of Parents in Helping Children Choose a College Major: The Role of Parents in Helping Children Choose a College Major - Zahira Rafeyfa Permana; Sinta Agustina; Arazka Aznur Fadilisyakur; Maulia Depriya Kembara (Jurnal Ilmu Sosial Politik dan Humaniora (JISORA), 2024)
The phenomenon of children choosing the wrong major in high school students who want to continue to the university level has become a common thing. This will have an impact on the quality of learning during college so that it will affect their future. This study aims to identify the role of parents in decision-making related to the selection of study programs and universities. Grade 12 students were the subjects of this study with a sample of 35 people. This study uses a quantitative method, data collection is used using the survey method. The aspects identified include parental support and involvement in helping children choose courses and colleges. This study results in 80% of parents are involved in choosing the study program and college that their child wants. In the final decision, 54% of children choose study programs and colleges of their own choice and 46% are the choice of parents. This research is the basis for the school's information to further develop the potential of students to find out early on students' interests and talents and also the school can involve parents in providing information about study programs, colleges, and future careers that can be pursued by their children.